Attitudes toward physical education and activity preferences of college students of De La Salle University, Manila - Anteola, Thelma B. (Animo Repository, 2011)
The purpose of this study is to determine the attitudes toward physical education and activity preferences of physical education students of De La Salle University, Manila for school-year 2011-2012. The study used the descriptive method for its design using a survey questionnaire given at random to 137 physical education students. The attitude inventory in different categories are tested and analyzed statistically with the use of mean and percentage while results of the factors affecting attitudes and activity preferences were ordered-rank. The results suggested that the students generally have a favorable attitude toward physical education. Ten most popular physical education activities students know and participate in regularly are the following: badminton, table tennis, volleyball, swimming, basketball running, bowling, line dance, modern dance hip/hop, and ballroom dance. Factors promoting positive attitude in physical education include: involvement in physical education activities which are of students' choice, general improvement of health involvement in physical activities during the grade school and high school days, and involvement of the family members in physical education.